2014
DOI: 10.1002/cncy.21437
|View full text |Cite
|
Sign up to set email alerts
|

CD117: A novel ancillary marker for papillary thyroid carcinoma in fine‐needle aspiration biopsies

Abstract: BACKGROUND: c-KIT/CD117 down-regulation has been described in papillary thyroid carcinoma (PTC). In this study, the authors investigated CD117 as an ancillary immunocytochemical test for PTC in fine-needle aspiration biopsy (FNAB). METHODS:The expression of CD117 was assessed in cytologic samples of histologically confirmed classic PTC (n 5 35) and in a control group of benign thyroid nodules (BTNs) (n 5 30) using immunocytochemistry. The corresponding PTCs and BTNs from surgical resection specimens also were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…On the other hand, CD117 expression level also showed nice performance characteristics in a sample pool with various cytological diagnosis (sensitivity = 92.48 %, specificity = 89.36 %, AUC=0.931, p<0.001) when used alone. Our results were in consistency with previous studies [8,11].…”
Section: Discussionsupporting
confidence: 96%
See 2 more Smart Citations
“…On the other hand, CD117 expression level also showed nice performance characteristics in a sample pool with various cytological diagnosis (sensitivity = 92.48 %, specificity = 89.36 %, AUC=0.931, p<0.001) when used alone. Our results were in consistency with previous studies [8,11].…”
Section: Discussionsupporting
confidence: 96%
“…Pusztaszeri et al revealed a clear divergence in CD117 expression level between PTC and benign thyroid nodules, where benign thyroid nodules and normal thyroid follicular tissue expressed a high level of CD117, while PTC expressed no or low level of CD117 protein, resulting in a 100 % sensitivity and specificity for a mono parameter [8]. However, their study only enrolled cytologically benign and PTC cases and the validity on indeterminate or suspicious cases remained unrevealed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…More recently, other studies have been published showing a decreased c-KIT expression in PTC compared to normal thyroid tissues [27, 28]. Several mechanisms have been described that can mediate the downregulation of c-KIT, including dysregulated expression of specific microRNAs [29] (miR-146b, miR-221, and miR-222) and promoter hypermethylation [12]; however, there are no studies that investigate this events in thyroid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 331 TMA were selected and included; classic PTC (60), FVPTC (48), follicular carcinoma (FC) (27), AC (14), MC (2), follicular adenoma (FA) (8) and BTN (172). Donor blocks were selected.…”
Section: Tissue Microarraysmentioning
confidence: 99%